Competência informacional e a busca de informações científicas: um estudo com pós-graduandos da Faculdade de Ciências Agronômicas da UNESP campus de Botucatu - Guerrero, Janaína Celoto [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The research deals with the issue information literacy, specifically on the search for scientific information for graduate students in education post-graduation in Agricultural Sciences and Forestry Science, whose main objective is to verify the performance of graduate students in search of scientific information. Its specific objectives: a) develop an instrument to assess the information literacy of the participants in the search for scientific information, b) whether the participants know and use Boolean operators in developing search strategies, c) whether the participants are familiar with the development of search strategies, d) investigate how the participants tend to use sources of information for the development of research, e) raise subsidies for training programs for users of the Library of the Faculty of Agronomic Sciences, UNESP, Botucatu, that assist the development of information competencies. For data collection a questionnaire was elaborated based on information literacy standards for higher education developed by the Association of College and Research Libraries, American Library Association, and also in international research on the subject. The questionnaire was administered via the Internet to students of the Post-graduate degree in Agronomy and Forest Science, Faculty of Agronomic Sciences, UNESP, Botucatu. The results showed that students generally have difficulty in the use of Boolean operators, the development of search strategies and the use of search tools available, whether the databases or electronic catalogs. The inclusion of policies on skills in informational classes and courses taught by the Library can improve the performance of students in the use of information resources.

A pesquisa trata do tema competência informacional, especificamente sobre a busca de informações científicas por pós-graduandos no ensino de pós-graduação nas áreas de Ciências Agronômicas e Ciência Florestal, cujo principal objetivo é verificar o desempenho dos pósgraduandos na busca de informações científicas. Tem como objetivos específicos: a) elaborar um instrumento para avaliar a competência informacional dos participantes na busca de informações científicas; b) verificar se os participantes conhecem e utilizam os operadores booleanos na elaboração de estratégias de busca; c) verificar se os participantes estão familiarizados com a elaboração de estratégias de busca; d) investigar como os participantes costumam utilizar fontes de informação para o desenvolvimento de pesquisas; e) levantar subsídios para os programas de capacitação dos usuários da Biblioteca da Faculdade de Ciências Agronômicas, da UNESP, campus de Botucatu, que auxiliem o desenvolvimento de competências informacionais. Para a coleta de dados foi elaborado um questionário com base em normas de competência informacional para ensino superior desenvolvidas pela Association of College and Research Libraries, da American Library Association, e também em pesquisas internacionais sobre o tema. O questionário foi aplicado via internet aos alunos dos Programas de Pós-graduação em Agronomia e Ciência Florestal da Faculdade de Ciências Agronômicas, UNESP, campus de Botucatu. Os resultados demonstraram que os alunos de modo geral possuem dificuldade no uso dos operadores booleanos, na elaboração das estratégias de busca e na utilização das ferramentas de buscas disponíveis, sejam as bases de dados ou os catálogos eletrônicos. A inclusão de políticas de desenvolvimento das competências informacionais nas aulas e cursos...
Keywords: Estudo de usuários - Bibliotecas universitárias; Educação de usuários - Bibliotecas universitárias; Bibliotecas universitárias; Competência em informação; Capacitação de usuários; Competência informacional; User studies; Academic libraries; Information literacy; Users training